Insight into the Functionality of Microbial Exopolysaccharides by NMR Spectroscopy and Molecular Modeling - Larsen, Flemming H.; Engelsen, Søren B. (Frontiers in Microbiology, 2015)
Microbial polysaccharides represent an important class of microbial polymers with diverse functions such as biofilm formation, thickening and gelling properties as well as health-promoting properties. The broad range of exopolysaccharide functionalities has sparked a renewed interest in this class of molecules. Chemical, enzymatic as well as genetic modifications by metabolic engineering can be used to create large numbers of analogous exopolysaccharide variants with respect to exopolysaccharide functionality. While this top-down approach is effective in finding new candidates for desired functionality, there seems to be a lack of the corresponding bottom-up approach. The molecular mechanisms of the desired functionalities can be established from NMR and molecular models and it is proposed that these models can be fed back into the biotechnology by using a quantitative structure-property approach. In this way it will be possible to tailor specific functionality within a given design space. This perspective will include two well-known commercial microbial exopolysaccharide examples namely gellan and diutan and show how even a limited use of multiphase NMR and molecular modelling can increase the insight into their different properties, which are based on only minor structural differences.